FORMULATION AND EVALUATION OF MEMBRANE-CONTROLLED TRANSDERMAL DRUG DELIVERY OF TOLTERODINE TARTARATE - P.K., LAKSHMI.; S., PAWANA.; RAJPUR, APARANJITHA; D., PRASANTHI. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The objective of the study was to formulate and evaluate membrane-controlled transdermal delivery system of Tolterodine tartrate (TT). Methods: TT membrane controlled transdermal patches were prepared by fabricating drug reservoir in a rate controlling membrane. Drug reservoir gel was prepared by using various polymers, rate controlling membrane is prepared by solvent casting method using Eudragit RL100 and RS100 in different ratios and was evaluated. The optimized formulations were fabricated and evaluated. Results: The membrane controlled transdermal patch of TT was optimized with HPMC K4 M gel (2.5%) and Eudragit RL100 & RS100(8:2) for rate controlling membrane. In-vitro, ex-vivo studies were conducted on rat abdominal skin and release at Q12 was 52.98Â±1.12Î¼g/cm2 for F3 formulation over the control (8.85Â±0.74 Î¼g/cm2). The flux was 3.574 Î¼g/cm2/hr, lag time was 0.8 hrs, permeability coefficient was 1.068 cm/hr and permeation was enhanced by 2.33 fold for F3 formulation. Conclusions: Out of the prepared formulations the F3 transdermal patch was optimized having a steady state transdermal flux of 3.574 Î¼g/cm2/hr, lag time of 0.8 hrs, enhancement ratio of 2.33 with permeability coefficient of 1.068 cm/hr and was subjected to ANOVA. ANOVA results showed significant difference between control and F3 in all skin permeation parameters. The optimized formulation (F3) exhibited controlled drug release profile with zero order kinetics and Fickian diffusion mechanism. . Keywords: Membrane controlled transdermal system, Tolterodine Tartarate, Hydroxypropyl methylcellulose, Eudragit RL100, Eudragit RS100 .